Maternal mortality: epidemiological profile of a state of northeast Brazil (Research, Society and Development, 2020)
The present study aims to analyze the epidemiological profile of maternal mortality in the State of Alagoas in the period between 2009 and 2018, through a quantitative approach, the study being of the descriptive and ecological type, using a public secondary data source. 290 maternal deaths of women residing without status in Alagoas were identified in the analyzed period, the majority (38.3%) in the age group of 20 to 29 years old, brown (72.8%), with 1 to 7 years of study (41.4%), single (46.6%), with 74.5% of deaths due to direct obstetric cause in the perinatal period; of all deaths in the analyzed period, 92.1% occurred in the hospital environment and the first causes was hypertensive syndromes (20.3%). It is concluded that the epidemiological profile of maternal mortality in Alagoas is known to be similar to the Brazilian profile and different from the world reality in relation to the main cause of deaths.